THE EFFECT OF THE COACH-ATHLETE RELATIONSHIP ON THE ATHLETES’ LEVEL OF ANGER - ŞAHİN, Tolga and GÖNEN, Mevlüt (Sportif Bakış: Spor ve Eğitim Bilimleri Dergisi, 2019)
This study aimed at searching the effect of the coach-athlete relationship on the athletes’ level of aggression. As the sample of the study, 420 athletes voluntarily participated in the survey. Two hundred forty-three of the participants were taekwondo athletes (107 female & 136 male), 177 were protected football player. In the study to obtain data in addition to demographic information form, the "Coach-Athlete Relationship Inventory Athlete Form" and "Multi-Dimensional Aggression Scale" were used. The collected data were analyzed by SPSS 20 package program. The multi-regression analysis used to determine the correlation between the coach-athlete relationship and the aggression level of the participants. According to analyze results, there was a negative and moderate correlation between the level of the coach-athlete relationship and the aggression, however; there was a positive and moderate correlation between the calmness level of the athletes. Therefore, we can say that if the coach-athlete relationship increases, the aggression level decreases. Moreover, the coach-athlete relationship is determined to be a meaningful indicator of athletes’ aggression levels.